Sex Determination Using Hand Morphometric Parameters in Individuals from Pakistani Descent - Ramsha Urooj Baig; Ramlah Naz; Mehreen Fatima; Zille-Huma; Munazza Obaid Suharwardy; Shaikh Jehanzaib Saeed; Fouzia Naeem Effendi; Inam E Khuda (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
Objective: To identify the presence or absence of sexual dimorphism using hand measurements alone in people from Pakistan. Moreover, to identify the variable that can be better at predicting sex among the rest of hand measurements. Methods: The research involved 122 male and 182 female participants, ranging in age from 18 to 60 years, without any hand deformities or missing fingers. Each participant underwent a set of hand measurements, including hand breadth, which was measured in a linear line from the lateral-most end on the head of the second metacarpal to the medial end on the head of the fifth metacarpal in centimeters. Additionally, hand length measured to be as the direct distance from the midpoint of the distal wrist crease to the top most point of the middle finger in centimeters. Logistic regression was used to analyze six hand measurements on the likelihood of prediction of the male or female gender Results: The logistic regression model showed statistical significance, ÷2 = 19.502, p < .012. The model explained 58.0% (Nagelkerke R2) of the variance in gender and accurately identified 84.2% of cases. A statistically substantial disparity was evident in hand measurements and hand indices across genders. (P-value=.0001). Conclusion: Our study reveals the presence of sexual dimorphism in hand morphometric parameters among the population of Pakistan. Hand measurements prove to be a reliable indicator for predicting gender in the majority of cases. Nevertheless, relying on a single hand measurement may not yield accurate gender predictions. Instead, a combination of various hand measurements can enhance the overall reliability of gender prediction.